Organizações sociais de saúde: estudo da estruturação e operacionalização no Município de Contagem - Alexandre Viana Barros de Andrade (2020)
Brazil’s Administrative Reform Project (BARP) deals with a great reform process, which has decentralization as its main axis. Throughout this process, operation actions have been transferred to the so-called non-state public sector, which is represented by social organizations (SO). Thus, market stays in charge of the production of goods and services. Health social organizations (HSO) are taken as one of the presentation standards of the third sector, and they are featured as a new category. It is aimed at the social function of management and health services suply, linked to the model of public-private parnerships. Due to the fact that it is presented as trend and a complex process, which can bring about relevant social political and economic changes, this study tried to understand how the structuring and operationalization process of an HSO happens. It raises critical factors, impacts, complexity, risks and uncertanties intrinsic to the process, as well as whether it is possible to outline strategies for HSO structuring and operationalization to take place in an effective way. For this purpose, the work was based on a qualitative approach with a descriptive and exploratory character. Data collecting method was a semistructured interview, with the content analysis technique for data treatment. It was possible to understand that it is a complex process with political, social and economic impact, one that requires the adoption of strategies to enhance the effectiveness of HSO structuring and operationalization. There is hope that, because of the issue relevance, results contribute to knowledge about difficulties, complexity, impacts and risks that are within the process. In addition, it is hoped that it helps creation of strategies which can relieve such factors, present in the model structuring and operationalization.